PENGELOLAAN KEGIATAN EKSTRAKURIKULER DI SEKOLAH SDN CIPAKU 03 DAN SD ISLAM AR-RIDO - Ai Lisnawati; Nur Laeli Asyahidah; Ridha Haifarashin; Agus Mulyana (STKIP Subang, 2023)
This research aims to describe the management of extracurricular activities at SDN Cipaku 03 and at SD Islam Ar-Rido. The research uses qualitative descriptive methods. The research subjects were extracurricular coaches and trainers at schools. Data collection techniques were carried out using observation, interviews and documentation. Data analysis is carried out using data collection, data reduction, data presentation, inference and/or verification techniques. The research results show that the management of extracurricular activities that have been implemented includes planning, organizing, implementing and evaluating processes. Through creative activities such as extracurricular activities which have goals and principles as guidelines for their implementation, extracurricular activities are able to bridge students in the process of developing students' potential, interests and talents.